Analisis Kelayakan Usaha Pada UMKM Alumnistore Indonesia Di Kabupaten Jombang - Hariyanti, Fadilah Fajar Imama; Rahmawati , Ita (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze and determine the level of business feasibility in the Indonesian Alumnistore convection MSME located in Jombang Regency using a quantitative descriptive research approach. This study examines two main aspects, namely non-financial aspects and financial aspects. Data related to non-financial aspects are analyzed using qualitative techniques through an assessment of business feasibility indicators, while financial aspect data are analyzed quantitatively using the investment criteria assessment method. The results of the non-financial aspect analysis indicate that from the market and marketing side, the business has fulfilled the marketing mix elements (product, price, promotion, and distribution). In the technical and technological aspects, product planning, technology selection, location determination, layout, inventory management, and quality control have been in accordance with feasibility standards. Management and human resource aspects are also considered feasible, reviewed from the labor procurement system, compensation, integration, maintenance, and termination of employment. From the legal aspect, the business has complete legality, and in the environmental aspect it has fulfilled the AMDAL requirements. Meanwhile, the results of the financial analysis show a Payback Period (PP) value of 3 years and 27 days; The Net Present Value (NPV) is Rp95,820,887; the Internal Rate of Return (IRR) is 26.98%; the Profitability Index (PI) is 1.19; and the Accounting Rate of Return (ARR) is 74.5%. Based on the overall analysis results, the Alumnistore Indonesia convection is declared feasible to run and develop.